1995
DOI: 10.3354/dao022025
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a toga-like virus from farmed Atlantic salmon Salmo salar with pancreas disease

Abstract: Pancreas disease (PD) of farmed Atlantic salmon Salmo salar has been recognised in Scotland, Ireland, Norway, the USA, France and Spaln and can cause severe economlc loss Thls paper reports the ~solatlon, flom PD-affected f~s h , of a virus with physicochemlcal characteristics and moiphology resembling members of the Togavirldae When Inoculated into Atlantic salmon post-smolts it causes pathological changes in pancreas h e a~t and muscle tlssues which are ind~stinguishable from those piesent in fleld outbreaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 7 publications
(15 reference statements)
5
138
0
Order By: Relevance
“…The salmon in 11 of these farms were moderately to strongly infected with Paranucleospora theridion, and their tissues contained low to moderate amounts of SAV. It has been thoroughly demonstrated that SAV play an important role in the development of PD (Nelson et al 1995, McLoughlin et al 1996, and high mortalities have been reported (Taksdal et al 2007, Fringuelli et al 2008. However, as several challenge experiments have shown (McLoughlin et al 1996, Desvignes et al 2002, Christie et al 2007), SAV might not be solely responsible for the PD outbreaks that occur in marine farms for salmonids.…”
Section: Pancreas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The salmon in 11 of these farms were moderately to strongly infected with Paranucleospora theridion, and their tissues contained low to moderate amounts of SAV. It has been thoroughly demonstrated that SAV play an important role in the development of PD (Nelson et al 1995, McLoughlin et al 1996, and high mortalities have been reported (Taksdal et al 2007, Fringuelli et al 2008. However, as several challenge experiments have shown (McLoughlin et al 1996, Desvignes et al 2002, Christie et al 2007), SAV might not be solely responsible for the PD outbreaks that occur in marine farms for salmonids.…”
Section: Pancreas Diseasementioning
confidence: 99%
“…It is well documented that 'pancreas disease' is associated with the presence of different strains of SAV (Nelson et al 1995, McLoughlin et al 1996, Villoing et al 2000, Hodneland et al 2005, Fringuelli et al 2008). However, the observed disease and mortality in salmon and rainbow trout farms are different from what can be seen in challenge experiments using the different SAV strains .…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Acute and chronic pancreatic lesions in exocrine pancreatic tissue may also be present in diseased fish (McLoughlin et al, 2002). The virus responsible for pancreas disease in Ireland and Scotland have been isolated and identified as an alphavirus, and the name salmon pancreas disease virus (SPDV) was suggested (Nelson et al, 1995; 2000; Weston et al, 1999). Because pancreas disease affected fish from Norway show similar clinical symptoms and gross pathology, it has been of the common opinion that pancreas disease in the British Isles and Norway is caused by the same virus.…”
Section: Introductionmentioning
confidence: 99%
“…Since then it has also been described in North America (Kent & Elston 1987), Ireland (Murphy et al 1992) and Norway (Poppe & Breck 1989). The condition is now known to be caused by infection with an alphavirus that is closely related to the virus responsible for sleeping disease (SD) in farmed rainbow trout Oncorhynchus mykiss (Nelson et al 1995, McLoughlin et al 1996, 2002, Castric et al 1997, Weston et al 1999, Villoing et al 2000. The name salmonid alphavirus (SAV) has been proposed for this closely related group of viruses (Weston et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulties inherent in isolating the virus from tissues of affected fish (Nelson et al 1995), traditionally, these histopathological changes have been the basis on which PD is diagnosed. More recently, tests capable of screening large numbers of sera for the presence of both SAV viraemia and virus neutralising antibodies have been developed and evaluated for routine diagnostic and epidemiological use (Graham et al 2003, Jewhurst et al 2004.…”
Section: Introductionmentioning
confidence: 99%